High prevalence of norovirus and rotavirus co‐infection in children with acute gastroenteritis hospitalised in Brazzaville, Republic of Congo. Issue 12 (28th November 2019) - Mikounou Louya, Vivaldie; Nguekeng Tsague, Boris; Ntoumi, Francine; Vouvoungui, Christevy; Kobawila, Simon Charles
Abstract: Objective: To evaluate the clinical severity of diarrhoea associated to viral co‐infection in children with acute gastroenteritis. Methods: About 461 children under five years hospitalised with acute diarrhoea (266 males and 187 females) were enrolled in the study. Using stool samples, rotavirus and adenovirus infections were investigated by ELISA, and norovirus infections by nested duplex RT‐PCR. We assessed social, demographic, clinical and behavioural conditions that might influence the occurrence of rotavirus, adenovirus and norovirus infections. Results: Mono‐viral infection was detected in 49% and mixed viral infection in 12% of patients. The prevalence of mixed infection was neither dependent on age nor sex. Three samples were infected with all three viruses. A significant association was found between fever (axillary temperature> 37.5 °C) and rotavirus–norovirus dual infection (aOR (CI 95%) = 2.1 (1.14–3.84), P  = 0.016; aOR (CI 95%) = 0.37 (0.19–0.73), P  = 0.004). Mixed infection was the most common during the dry season from June to October (71.4% versus 54.7%, P  = 0.023). Conclusion: Co‐infection with both rotavirus and norovirus is common in under‐five hospitalised children but does not contribute to the severity of the disease. Abstract : Objectif: Evaluer la sévérité clinique de la diarrhée associée à la coinfection virale chez les enfants atteints de gastroentérite aiguë. Méthodes: 461 enfants de moins de cinq ans hospitalisés pour une diarrhée aiguë (266 garçons et 187 filles) ont été inclus dans l'étude. Sur des échantillons de selles, les infections à rotavirus et à adénovirus ont été investiguées par ELISA et les infections à norovirus par RT‐PCR duplex imbriqué. Nous avons évalué les conditions sociales, démographiques, cliniques et comportementales susceptibles d'influencer la survenue d'infections à rotavirus, adénovirus et norovirus. Résultats: Une infection mono virale a été détectée chez 49% des patients et une infection virale mixte chez 12% des patients. La prévalence des infections mixtes ne dépendait ni de l'âge ni du sexe. Trois échantillons étaient infectés par tous les trois virus. Une association significative a été observée entre la fièvre (température axillaire > 37, 5 °C) et la double infection rotavirus‐norovirus (aOR (IC95%) = 2, 1 (1, 14–3, 84), P  = 0, 016; aOR (IC95%) = 0, 37 (0, 19–0, 73), P  = 0, 004). Les infections mixtes étaient les plus courantes pendant la saison sèche de juin à octobre (71, 4% contre 54, 7%, P  = 0, 023). Conclusion: La coinfection à la fois par le rotavirus et par le norovirus est fréquente chez les enfants de moins de cinq ans hospitalisés, mais ne contribue pas à la sévérité de la maladie.